Learning Interest: How Effective is Kahoot-Based Digital Game Based Learning Model? - Novitriani, Ganis; Nurul Azizah; Umi Hijriah; Baharudin; Riyan Terna Kuswanto (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze the effectiveness of the Game-Based Learning (GBL) model using the Kahoot game in enhancing the interest in learning Islamic Religious Education (PAI) at SMA Negeri 15 Bandar Lampung. The research employs a quantitative experimental approach with a quasi-experimental design. The experimental class is class X.2, while class X.6 serves as the control group. This study proposes a different approach by integrating the Game-Based Learning model using Kahoot with students' learning interest, particularly in PAI. The implications of this research highlight the importance of integrating technology in PAI learning and the necessity for teachers to develop innovative and relevant teaching strategies for the future. The results of the normality test indicate a significance of 0.200 (data is normally distributed), and the homogeneity test shows a significance of 0.893 (data is homogeneous). The t-test results show significance values of 0.204 and 0.201, which means that the sig (2-tailed) values of 0.204 < 0.05 and 0.201 < 0.05, leading to the conclusion that is accepted and is rejected, indicating that the Game-Based Learning model using Kahoot is not effective in improving students' interest in learning.